Kapin (Smart Card) Media: Evaluating Learning Tools Efficacy to Improve Reading Skills of Second Grads - Kristina Maisaroh; Laila , Alfi; Basori , Muhamad (Utamax : Journal of Ultimate Research and Trends in Education, 2023)
In the context of classroom learning, particularly at the elementary school level, various methods are employed. This study aims to achieve three key research objectives: (1) to establish the reliability of Chapin learning media, (2) to ensure its effective implementation, and (3) to assess its overall efficacy. The research methodology utilized the Research and Development (R&D) approach, following the Addie development model, consisting of five stages: Analysis, Design, Development, Implementation, and Evaluation. The study's population consisted of 12 students from Class II at SDN Tiron III and 23 students from Class II at SDN Tiron IV. Data collection involved the use of validation questionnaires for media, content, and learning specialists, supplemented by both small- and large-scale experiments. Data analysis encompassed validity testing, practicality assessment through teacher response questionnaires (involving 2 teachers and 35 students), and effectiveness evaluation based on students' learning outcomes, analyzed using the N-Gain Score. The results of this study indicate that the smart card learning media achieved a high level of validity, with percentages of 90%, 84%, and 84% for content, media, and overall validity, respectively. Furthermore, the practicality assessment revealed that students' responses averaged 88%, while expert teacher responses averaged 84%. The N-Gain score, with values of 0.77 for the wider class scale and 0.79 for the limited class scale, both fall into the high category, demonstrating the efficacy of the learning media.